(untitled) (Journal of actual problems of jurisprudence, 2025)
The relevance of this article lies in the fact that artificial intelligence (AI) technologies are currently being actively implemented in various spheres of society. In this regard, it is necessary to study the impact of AI on the law-making process, determine the directions of using international acts for legal practice and improving national legislation, and identify the risks of its application in lawmaking. The purpose of the article is to study the international experience of AI regulation and analyze its impact on law–making in the Republic of Kazakhstan. In the process of preparing the article, following scientific research methods were used: analysis and synthesis, systematic, comparative legal analysis, a review of scientific literature and regulatory documents was conducted, and the experience of countries implementing AI regulation was studied. As a result of the research, the experience of regulating AI in the European Union was systematized, the legal, ethical and technological aspects of using AI in law-making were considered, the need to develop AI regulatory mechanisms for Kazakhstan was substantiated, and relevant recommendations were proposed. The results of the research can be used by legislative bodies and legal experts as a basis for integrating AI into the legal system. The scientific article was prepared as part of the implementation of the grant project "Introduction of artificial intelligence tools into the legislative process of the Republic of Kazakhstan to optimize and increase the efficiency and transparency of legislation", funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (grant No. BR27101389). Keywords: artificial intelligence, legal regulation, lawmaking, international experience, digital transformation.